Human resource development: enhancing entrepreneurial potential in MSMEs - Rosita, Sry; Hasbullah, Husni; Yacob, Syahmardi (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2024)
This study aims to explore the role of micro, small, and medium enterprises (MSMEs) in human resource development by enhancing entrepreneurial potential. Qualitative data were obtained using a descriptive exploratory approach from in-depth interviews with 41 MSME actors assisted by the Jambi City Manpower, Cooperatives, and Small and Medium Enterprises Office during managerial and technical guidance in 2023. The data were analyzed thematically and narratively to capture respondents' views and reasons. The study identifies various aspects of MSMEs, including business types, ideals, vision, mission, goals, sources of ideas, creativity and innovation, threats, strengths, weaknesses, and opportunities. It also examines the impact of education and training on human resource development and entrepreneurial potential. The findings indicate that MSMEs leverage diverse sources of ideas and exhibit significant creativity and innovation to adapt to business trends. However, further studies are needed to measure the long-term impact of human resource development. Additionally, the study calls for examining external factors such as government policies, market conditions, and technological advancements that influence human resource development and entrepreneurial potential in MSMEs.